Synergistic effect of NiCr-Cr3C2 + Y2O3 to enhanced performance of Ti-based composite fabricated by laser cladding - Zhang, Zhiqiang (2024)
The surface modification technology, which is of great significance in aerospace, energy, and other fields, is based on reinforcement. In this study, a titanium-based composite material system, formed using laser cladding and based on NiCr-Cr3C2 + Y2O3 dual additives, was investigated. TiC reinforcement particles were generated in situ through the reaction between NiCr-Cr3C2 and Ti6Al4V during the cladding process. Additionally, Ni and Cr elements provided solid solution-strengthening effects to the matrix. Meanwhile, Y2O3 particles were introduced ex-situ, effectively eliminating defects in the coating and inhibiting the dendritic growth of TiC particles. This process enhanced the dispersion-strengthening effect of TiC. The titanium-based composite material, incorporating NiCr-Cr3C2 + Y2O3, exhibited excellent tribological performance, displaying a wear rate of approximately 4.22 × 10−4 mm3·N−1·m−1.